IMPLEMENTATION OF TELEMEDICINE AS AN EFFORT TO IMPROVE ACCESS AND QUALITY OF PUBLIC HEALTH SERVICES IN RURAL AREAS (STUDY AT JULOK PUBLIC HEALTH CENTER, EAST ACEH) - Mona Fandani; Kosasih (RADJA PUBLIKA, 2025)
The rapid growth of digital health technologies has enabled the adoption of telemedicine as an alternative solution to improve healthcare access and quality, particularly in rural communities with limited infrastructure. This study explores the implementation of telemedicine at Julok Community Health Center, East Aceh, using a qualitative descriptive-exploratory design. Eight key informants, including health workers and patients, were interviewed and observed. The data were analyzed thematically using Miles and Huberman's framework through coding, data reduction, display, and conclusion drawing. Results reveal that telemedicine significantly improves access and responsiveness of healthcare services but faces barriers such as unstable internet connectivity and limited patient digital literacy. Strengthening digital infrastructure, providing consistent training for medical staff, and enhancing community awareness are crucial to optimize telemedicine implementation.